Pengembangan Virtual Laboratory pada Materi Inovasi Teknologi Biologi untuk Meningkatkan Pemahaman Konsep Siswa Kelas X SMA - Arica Pavitasari; Dian Puspita; Mar’atus Sholihah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the feasibility and impact of virtual laboratories in learning the material of innovation in biological technology (biotechnology) for high school students in grade X. The feasibility assessment was carried out by three expert validators using a questionnaire instrument that measured aspects of material, media, and language and based on readability tests by teachers and students. The results of the study showed that the percentage of validity of the Virtual Laboratory from material experts was 95%, media experts 83%, language experts 90% with the third category being